PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN PADA CANGKIR HOUSE OF COFFEE AND TEA TEMANGGUNG - Anggun Kusumaningtyas, 14.05.51.0151; Rizal, Alimuddin (Students' Journal of Economic and Management, 2018)
Along with the growth of the culinery business in Temanggung, causing the increasingly high level of competition faced by Cangkir House of Coffee and Tea. This research tests there independent variables they are product quality, service quality and perceived price that can affect variable dependent it is consumer satisfaction. Population of this research are consumers of Cangkir House Of Coffee and Tea. Samples were taken of 100 respondents by using non-probability sampling technique with the purposive sampling approach. Data was collected by using a survey method through quetionnaires which were filled out by consumers. Then the data obtained were analyzed using multiple linear regression analysis. The result showed that the variables product quality, service quality and price perception had a positive influence on customer satisfaction. Keywords: Product Quality, Sevice Quality, Perceived Price, Consumer Satisfaction